Worker-Born Males Are Smaller but Have Similar Reproduction Ability to Queen-Born Males in Bumblebees - Huiyue Zhao (MDPI AG, 2021)
Queen-worker conflict over the reproduction of males exists in the majority of haplodiplioidy hymenpteran species such as bees, wasps, and ants, whose workers lose mating ability but can produce haploid males in colony. Bumblebee is one of the representatives of primitively eusocial insects with plastic division labor and belongs to monandrous and facultative low polyandry species that have reproductive totipotent workers, which are capable of competing with mother queen to produce haploid males in the queenright colony compared to higher eusocial species, e.g., honeybees. So, bumblebees should be a better material to study worker reproduction, but the reproductive characteristics of worker-born males (WMs) remain unclear. Here, we choose the best-studied bumblebee Bombus terrestris to evaluate the morphological characteristics and reproductive ability of WMs from the queenless micro-colonies. The sexually matured WMs showed smaller in forewing length and weight, relatively less sperm counts but equally high sperm viability in comparison with the queen-born males (QMs) of the queenright colony. Despite with smaller size, the WMs are able to successfully mate with the virgin queens in competition with the QMs under laboratory conditions, which is quite different from the honeybees reported. In addition, there was no difference in the colony development, including the traits such as egg-laying rate, colony establishment rate, and populations of offspring, between the WM- and the QM-mated queens. Our study highlights the equivalent reproductive ability of worker-born males compared to that of queens, which might exhibit a positive application or special use of bumblebee rearing, especially for species whose males are not enough for copulation. Further, our finding contributes new evidence to the kin selection theory and suggests worker reproduction might relate to the evolution of sociality in bees.